(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role of individual approaches in teaching the English language, emphasizing learner-centered methodologies. As education increasingly prioritizes differentiated instruction, understanding the psychological, cognitive, and sociocultural factors that shape language learning is essential. Drawing on research from applied linguistics, educational psychology, and second language acquisition (SLA), this paper discusses strategies for implementing individualized instruction in English language classrooms and evaluates their effectiveness in fostering learner autonomy, motivation, and language proficiency.